Clinical Holistic Medicine: The Dean Ornish Program (“Opening the Heart”) in Cardiovascular Disease - Søren Ventegodt; Efrat Merrick; Joav Merrick (The Scientific World Journal)
Dean Ornish of the Preventive Medicine Research Institute in Sausalito, California has created an intensive holistic treatment for coronary heart patients with improved diet (low fat, whole foods, plant based), exercise, stress management, and social support that has proven to be efficient. In this paper, we analyze the rationale behind his cure in relation to contemporary holistic medical theory. In spite of a complex treatment program, the principles seem to be simple and in accordance with holistic medical theories, like the Antonovsky concept of rehabilitating the sense of coherence and the life mission theory for holistic medicine. We believe there is a need for the allocation of resources for further research into the aspects of holistic health and its methods, where positive and significant results have been proven and reproduced at several sites.